Teachers, Schools, and Society - Miller Sadker David (McGraw Hill, 2007)
The new contents for this edition: Privious users of teachers, school and society will find the student-friendly writting style, engaging features, amd many of the chapters and topics familiar. But when we revise a texbook, we want those revisions to be meaningful and current. Reforming schools and President Obama's education program are two such consequential revisions. Other changes, such as the sections on teacher liability, provetty, and classroom mangement. we suggessted by professors using the book.